An integrative approach to correcting the physical condition of pupils of secondary schools during physical training as a pedagogical problem = Інтегративний підхід до корекції фізичного стану учнів ЗНЗ під час занять фізичною культурою як педагогічна проблема - Schislovsky, S. V.; Iedinak, G. A.; Zaikin, A. V. (Journal of Education, Health and Sport, 2016)
Schislovsky S. V., Iedinak G. A., Zaikin A. V. An integrative approach to correcting the physical condition of pupils of secondary schools during physical training as a pedagogical problem = Інтегративний підхід до корекції фізичного стану учнів ЗНЗ під час занять фізичною культурою як педагогічна проблема. Journal of Education, Health and Sport. 2016;6(10):653-667. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221371 http://ojs.ukw.edu.pl/index.php/johs/article/view/4110 https://pbn.nauka.gov.pl/sedno-webapp/works/771253 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 21.10.2016. ІНТЕГРАТИВНИЙ ПІДХІД ДО КОРЕКЦІЇ ФІЗИЧНОГО СТАНУ УЧНІВ ЗНЗ ПІД ЧАС ЗАНЯТЬ ФІЗИЧНОЮ КУЛЬТУРОЮ ЯК ПЕДАГОГІЧНА ПРОБЛЕМА С. В. Сцісловський Кам’янець-Подільський національний університет імені Івана Огієнка, Україна; Г. А. Єдинак Львівський державний університет фізичної культури, Україна; А. В. Заікін Кам’янець-Подільський національний університет імені Івана Огієнка, Україна Анотація. Проаналізовано інформацію документальних матеріалів і наукової літератури, пов’язану з підходами, що на сучасному етапі є провідними у корекції фізичного стану учнів загальноосвітнього навчального закладу під час занять фізичною культурою. Встановлено недостатню дієвість підходів, що використовуються під час занять фізичною культурою для вирішення завдання з поліпшення показників фізичного стану учнів. Виявлено, що перспективним є використання інтегративного підходу, який передбачає врахування стійких форм інтегральної індивідуальності кожного учня. Однією з таких форм є тип соматичної конституції, а представники існуючих типів відрізняються за значеннями більшості показників фізичного стану. У зв’язку з цим один із перспективних напрямів розв’язання проблеми, що розглядається, полягає в урахуванні в учнів таких типів і наданні представникам кожного з них програми, виконання якої забезпечить поліпшення їх фізичного стану. Kлючові слова: фізична культура, загальноосвітня школа, учні, соматотип. Schislovsky S. V., Iedinak G. A., Zaikin A. V. An integrative approach to correcting the physical condition of pupils of secondary schools during physical training as a pedagogical problem. Summary. The information was analyzed and documentary material scientific literature relating to approaches that are at present major correction in the physical condition of students of an educational institution during their physical training. Established lack of effectiveness of approaches used during physical training for the task of improvement in the physical condition of students. Revealed that promising is to use an integrative approach that takes into consideration sustainable forms of integrated individuality of each student. One of these forms is the type of somatic constitution, and representatives of existing types differ in the values of most indicators of physical condition. In this regard, one of the promising directions of solving the problem in question is the account of the students and providing these types of representatives of each program, implementation of which will ensure improvement of their physical condition. Key words: physical education, secondary school, students, somatotype.